And then there was the one : a novel - Waters, Martha, 1988- (Atria Paperback, 2025)
"Set in 1930s England, in a quaint village in the Cotswolds, Georgiana Radcliffe has accidentally become an amateur detective after helping solve four murders in a single year. When the chairman of the village council turns up dead, everyone agrees with the official ruling of a heart attack, but Georgie can't help but suspect that the council chairman is a fifth victim. Now, murder tourists are flocking from around the country, in hopes of becoming sleuths themselves. Along with her reporter friend, she reaches out to a famous London detective for assistance in ascertaining why they have become a magnet for murder. But the fancy detective is simply too busy-or can't be bothered-to help, and instead dispatches his secretary, Sebastian Fletcher-Ford-a posh womanizer who, truthfully, is just trying to get out of his hair, much to practical, no-nonsense Georgie's dismay. But as they investigate in the charming Buncombe-upon-Woolly-with plentiful scones, sheep on the village green, and murder tourists at every turn-Georgie finds that her previous assessment of Sebastian may have been wrong, and rather than solving a murder, she may be solving for love instead." --